Analisis Keterkaitan Durasi Menonton Animasi Digital dengan Perkembangan Bahasa Anak Usia 4–6 Tahun di TK Sion Oepura - Dika Sonia Gloria Lasi; Credo G. Betty; Theodorina Novyani Seran; Angelikus N. Koten (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2026)
This study aims to analyze the relationship between digital animation viewing duration and language development among children aged 4–6 years at TK Sion Oepura. This study employed a qualitative descriptive method. The subjects consisted of four children aged 4–6 years, with four parents and two classroom teachers serving as supporting informants. Data were collected through direct observation and interviews and were analyzed through data collection, data reduction, data display, and conclusion drawing. Data trustworthiness was ensured through source and technique triangulation. The findings indicate that limited viewing duration of approximately one hour per day, accompanied by adult supervision, was associated with better language development tendencies, such as increased vocabulary, greater speaking confidence, and improved ability to understand instructions. Conversely, longer viewing duration, approximately 1.5–2 hours per day, particularly without consistent supervision, was indicated to be associated with lower concentration, unclear articulation, and reduced verbal social interaction. These findings highlight the importance of regulating viewing duration, selecting educational content, and providing active parental and teacher support so that digital animation can support children’s language development more proportionally.